Persistent Placoid Maculopathy: Lichen-like Lesions Growing between Retinal Pigment Epithelium and Bruch's Membrane - Li, Miaoling; Zhang, Xiongze; Wen, Feng; Ji, Yuying; Mi, Lan (Ophthalmology retina, 2024)
To report the novel imaging findings in persistent placoid maculopathy (PPM) from the first case series of Asian subjects. Retrospective observational case series. Patients with PPM from 2013 to 2023. Medical records and multimodal images from each visit were analyzed. Imaging and follow-up findings. Twenty-one eyes of 16 patients were included. Mean age was 61 (range, 48-84) years old. Five patients showed bilateral involvement. Persistent placoid maculopathy lesions were unremarkable on color fundus photography, autofluorescence, and fluorescein angiography. Hypofluorescent spots with a lichen-like appearance presented in all phases of indocyanine green angiography, which were most prominent in the late phase and presented in a fused (71%) or clustered (29%) pattern. The hypofluorescence correlated with the lesions between the retinal pigment epithelium (RPE) and Bruch's membrane (BM) with moderate reflectivity on OCT, and the thickness ranged from slit-like to mound-like. The intensity of hypofluorescence sometimes varied in the same eye and correlated with the thickness of sub-RPE lesions on OCT. No abnormal blood flow signals were detected in either the sub-RPE space or choriocapillaris slab of OCT angiography across the PPM lesions. Peripapillary (5 eyes, 24%) and extra posterior pole (2 eyes, 10%) involvements were seen, the former sparing the β zones of optic discs. Ten eyes of 7 patients were followed up (median, 26 months; range, 2-121 months). During follow-up, the lichen-like lesions spread and migrated slowly without changing the plane patterns of the first visit and were limited to sub-RPE growth. The fused lichen-like pattern sprawled around the enlarged base. The clustered lichen-like pattern gradually loosened. Ten eyes (48%, 9 eyes in the fused pattern, 1 eye in the clustered pattern) had secondary choroidal neovascularization (CNV) at the first visit, with type I (6 eyes, 5 of which were polypoidal choroidal vasculopathy) and type II (4 eyes). No new CNV developed during follow-up. Persistent placoid maculopathy lesions were located in the sub-RPE space, as determined by multimodal imaging. Spreading and migration between the RPE and BM may account for their unique lichen-like appearance and progression pattern. Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.